Digital Devices and Interpersonal Communication Over Time - Bratina, Tomaž (Revija za elementarno izobraževanje, 2023)
Digital communication supported by mobile devices has an essential impact on interpersonal relations. Face-to-face communication is significantly affected because of the habits of simultaneous use of mobile devices and digital communication. The effect on interpersonal relations is negative since the behaviour affects personal closeness, empathy, and trust, including the feeling that a physically present person is unwanted or redundant, even replacing face-to-face communication with text messaging. The behavioural patterns significantly change if a loved one is involved. Results show that behaviour patterns did not change considerably over five years. Simultaneous digital communication, replacing face-to-face contact or voice call with text messaging is still present, with minor deviations in the post-pandemic period. Nevertheless, personal contact with beloved persons is still the primary preference over time compared to digital contact.
Keywords: mobile devices, interpersonal communication, simultaneous digital communication, phubbing, text messaging